Social movements as agents of change: fighting intersectional food inequalities, building food as webs of life - Campos Motta, Renata (The sociological review, 2021)
What does the diversity of social movements and food initiatives tell us about processes of social change? I argue that they offer a productive analytical lens to observe social change because they identify injustices and dynamics of inequalities in the food system and are actively engaged in transforming these. Alternative local food initiatives react to the environmental impacts of globalized food relations; food sovereignty movements highlight class inequalities and power asymmetries in the food system that affect people?s rights to culturally appropriate foodways; food justice movements denounce institutional racism; feminist movements fight persistent gender inequalities from food production to consumption; vegan movements defend animal rights. These are often mapped onto different world regions, with food justice movements more present in the US; food sovereignty movements louder in the Global South; feminist food movements more active in Latin America; and local food movements commonly in the Global North. This article brings together diverse strands of activism and research on social inequalities related to food under the conceptual umbrella of food inequalities. In addition to concept building, it contributes to a sociology of food studies by mapping the geopolitics of knowledge about social change behind the growing mobilization around food issues.